Evaluasi Sistem Proteksi Kebakaran Ditinjau Dari Sarana Penyelamatan Dan Sistem Proteksi Aktif Pada Bangunan Politeknik Penerbangan - Ivana Wardani; Inda Tri Pasa; Fauziah Nur; Suherman (Universitas Serang Raya, 2024)
Problems: The problem of fire is a problem that is often faced both in Indonesia and other parts of the world. The safety of the people inside the building and its environment must be the main consideration, especially regarding the danger of fire, so a building must have a fire protection system, both active and passive, equipped with site equipment and rescue facilities. Purpose: The aim of this research is to determine the implementation of active protection systems and rescue facilities in the Medan Aviation Polytechnic Dormitory. To determine the level of reliability of the building safety system against fire hazards in the Medan Aviation Polytechnic Dormitory by evaluating the implementation of the fire protection system based on applicable regulations. Methodology: The method used in this research is a descriptive method. The primary data collection methods used were observation and interviews. The resource persons in this research were employees of the household or general department. The results of observations and interviews are linked to secondary data in the form of building evacuation routes, building population and regulations related to fire protection systems that apply in Indonesia. Results/Findings: The results of this research show that the evaluation of the active protection system in the Alpha, Delta and Bimtar dormitory buildings is <60, meaning the level of suitability is not at all appropriate. The rescue system, namely the exit, only exists in the delta building and is in a damaged condition. There are no exit markers in every building.Keywords: Fire Protection System, Building Protection